Value System in Learning Student Independence in Islamic Boarding School Environment in Indonesia - Mutia Hafizah; Firman; Dina Sukma (Konsultan Jurnal Ilmiah Indonesia, 2025)
The value system plays a crucial role in shaping the character and independence of students (santri) in Islamic boarding schools in Indonesia. These boarding-based educational institutions not only serve as a place for deepening religious knowledge but also as a medium for developing resilience, discipline, and responsibility. This article aims to explore how value systems are applied in fostering the independence of santri through daily activities, such as congregational prayers, time discipline, maintaining cleanliness, and performing routine tasks. The inculcation of Islamic values is consistently implemented to establish positive habits, develop a sense of responsibility, and instill an independent attitude. On the other hand, the challenges of globalization, including the influence of modern culture and technological advancements, test the relevance of traditional value systems within the Islamic boarding school environment. The findings indicate that the integration of religious and cultural values into the daily lives of santri has a significant impact on shaping their character. With a structured value system, santri not only excel in managing life within the boarding school but are also prepared to face life outside the school environment with responsibility and independence. This study recommends strengthening the synergy between traditional Islamic values and modern educational innovations to ensure the sustainability of character development for santri. In this way, Islamic boarding schools can continue to contribute to producing morally upright generations equipped to face the challenges of modern life.